2013
DOI: 10.1037/a0033983
|View full text |Cite
|
Sign up to set email alerts
|

Course of traumatic stress reactions in couples after a burn event to their young child.

Abstract: Both mothers and fathers are seriously affected by a burn event of their young child. Despite a general decrease over time, a subgroup of parents is at risk for chronic symptoms. The results call for the integration of prolonged parent support in family centered pediatric burn aftercare programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
53
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 31 publications
9
53
2
Order By: Relevance
“…Data were collected in three Dutch and four Belgian burn centres. In previous articles, we reported on acute stress and the course of parental stress symptoms in this sample [21,26]. Data for the current study concerning child behavioural and emotional problems were collected at 3 months (T1) and 12 months postburn (T2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were collected in three Dutch and four Belgian burn centres. In previous articles, we reported on acute stress and the course of parental stress symptoms in this sample [21,26]. Data for the current study concerning child behavioural and emotional problems were collected at 3 months (T1) and 12 months postburn (T2).…”
Section: Methodsmentioning
confidence: 99%
“…Mothers' emotional reactions were associated with their child's reactions after the burn event in several studies [10,11,25]. Information on emotional reactions and worries of fathers is very limited [11,21,22,26]. The few available studies have shown that within couples mothers may experience more stress symptoms than fathers [21,26], but fathers are unquestionably affected by their child's burn event as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The burn recovery process is long and caregiving for a loved one with a chronic problem can be stressful. One study found that 18% of mothers and 6% of fathers of pediatric burn survivors evidence significant traumatic stress symptoms 18 months after the injury [27]. Future studies could usefully investigate the range of interventions for psychosocial issues not covered in this paper such as the support provided when patients see their burns scars for the first time [28], the mode of delivery of psychosocial interventions and the support provided for young people transitioning into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Experiencing these symptoms over a long period of time can affect how well a parent is able to care for themselves and their child. Chronic parental PTSS has been also found to contribute to the development and maintenance of child PTSS (Bakker et al, 2013b;De Young et al, 2014). Therefore it is vital that parents' emotional needs are identified and appropriate support is provided.…”
Section: How Can Parents Themselves Be Affected When Supporting Theirmentioning
confidence: 99%